Cooperation‐mediated plasticity in dispersal and colonization. (24th August 2016) - Jacob, Staffan; Wehi, Priscilla; Clobert, Jean; Legrand, Delphine; Schtickzelle, Nicolas; Huet, Michele; Chaine, Alexis
Abstract : Kin selection theory predicts that costly cooperative behaviors evolve most readily when directed toward kin. Dispersal plays a controversial role in the evolution of cooperation: dispersal decreases local population relatedness and thus opposes the evolution of cooperation, but limited dispersal increases kin competition and can negate the benefits of cooperation. Theoretical work has suggested that plasticity of dispersal, where individuals can adjust their dispersal decisions according to the social context, might help resolve this paradox and promote the evolution of cooperation. Here, we experimentally tested the hypothesis that conditional dispersal decisions are mediated by a cooperative strategy: we quantified the density‐dependent dispersal decisions and subsequent colonization efficiency from single cells or groups of cells among six genetic strains of the unicellular Tetrahymena thermophila that differ in their aggregation level (high, medium, and low), a behavior associated with cooperation strategy. We found that the plastic reaction norms of dispersal rate relative to density differed according to aggregation level: highly aggregative genotypes showed negative density‐dependent dispersal, whereas low‐aggregation genotypes showed maximum dispersal rates at intermediate density, and medium‐aggregation genotypes showed density‐independent dispersal with intermediate dispersal rate. Dispersers from highly aggregative genotypes had specialized long‐distance dispersal phenotypes, contrary to low‐aggregation genotypes; medium‐aggregation genotypes showing intermediate dispersal phenotype. Moreover, highly aggregation genotypes showed evidence for beneficial kin‐cooperation during dispersal. Our experimental results should help to resolve the evolutionary conflict between cooperation and dispersal: cooperative individuals are expected to avoid kin‐competition by dispersing long distances, but maintain the benefits of cooperation by dispersing in small groups.